Urgensi Pengaturan Terhadap Marine Autonomous Surface Ships (MASS) dalam Pertanggungjawaban Pengangkutan Bahan Berbahaya - Muhammad Aqil Kamaluddin (Media Iuris, 2022)
AbstractThe era of globalization has encouraged developments in various sectors, including shipping. There is one emerging shipping technology, namely Marine Autonomous Surface Ships or MASS. Sheetal from the use of MASS, the development of this technology is not yet with a legal umbrella that explains the operation of MASS. Arrangements regarding MASS are needed to provide liability for what happens to the party if an event results in a loss in transportation using MASS. Furthermore, in the case of MASS transportation itself is engaged in the transportation of hazardous materials, then with the existence of a legal umbrella that provides safety for this responsibility, it can create transportation that ensures the safety and success of every party involved. AbstrakEra globalisasi mendorong perkembangan di berbagai sektor, termasuk pelayaran. Terdapat salah satu teknologi pelayaran yang muncul, yaitu Marine Autonomous Surface Ships atau MASS. Terlepas dari penggunaan MASS, perkembangan teknologi ini belum diimbangi dengan adanya payung hukum yang jelas atas pengoperasian MASS. Pengaturan mengenai MASS diperlukan untuk memberikan kejelasan pertanggungjawaban terhadap para pihak apabila terjadi peristiwa yang mengakibatkan kerugian dalam pengangkutan menggunakan MASS. Terlebih lanjut dalam hal pengangkutan MASS ini sendiri bergerak dalam bidang pengangkutan bahan berbahaya, maka dengan adanya payung hukum yang memberikan kejelasan terhadap pertanggungjawaban tersebut, maka dapat terciptanya pengangkutan yang menjamin keselamatan dan keberhasilan setiap pihak yang terlibat.